DESIGN OF A DECISION SUPPORT SYSTEM FOR CAREER RECOMMENDATION OF DIPLOMA III INFORMATICS MANAGEMENT STUDENTS AT UNIVERSITAS EKASAKTI PADANG USING THE PROFILE MATCHING METHOD - Danyl Mallisza; Nuraeni Dahri; Muhammad Bima Wahyu Utomo mallisza (Journal of Social and Economics Research, 2026)
Students of the Diploma III Informatics Management program at Universitas Ekasakti Padang often face difficulty determining a career path that matches their competencies, interests, and talents after graduation. A mismatch between a student's abilities and their chosen career can lead to poor performance and job dissatisfaction later on. This study aims to build a decision support model that provides career recommendations for students based on the compatibility between student competency profiles and the ideal profile of each information technology career. This study uses a descriptive quantitative approach within a Waterfall system-development framework (analysis, design, implementation, testing, and maintenance), applying the Profile Matching method as the data-analysis technique during the analysis and design stages. Profile Matching assumes there is an ideal predictor variable level that should be possessed rather than merely a minimum level that must be fulfilled. The calculation process includes determining assessment aspects (technical competence, non-technical competence, and interest), calculating the gap between the student profile and the ideal profile, weighting the gap values, grouping them into Core Factor and Secondary Factor, and calculating the total score and ranking. Data were collected through observation, interviews, and student self-assessment questionnaires. The results show that the Profile Matching method is able to produce a ranked list of career recommendations that match each student's competency profile, such as Programmer, Network Administrator, Database Administrator, or Technical Support, based on the highest final score obtained. This research is limited to the design and modeling of a decision support system using the Profile Matching method and does not yet cover full application development or testing on a large student population. This research contributes a decision-making model framework that can serve as a reference for study programs in developing computer-based career guidance systems for Diploma III Informatics Management students.